APLIKASI SISTEM PEMBERIAN REWARD BERDASARKAN KINERJA KARYAWAN DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA TOKO GOLDEN JAYA STAR PEKANBARU - Yuda Irawan; Nella Sari (Universitas Islam Kuantan Singingi, 2019)
The employee system at the Golden Jaya Star Pekanbaru Shop is currently based on the store's personal opinion, so its assessment of employee performance is not believed to be valid. This study aims to determine the employee performance appraisal system that is right used as the basis for awarding employee rewards. This research is expected to be able to help or facilitate the Golde Jaya Star Pekanbaru shop leader in providing rewards based on employee performance appraisal, among others, with the existence of this application can help leaders in giving rewards based on employee performance appraisal at the Golden Jaya Star Pekanbaru store. With this application, it can help leaders in giving rewards based on employee performance appraisals can reduce the occurrence of errors in the provision of employee rewards. With the application of the system of giving rewards based on employee performance evaluation can reduce the occurrence of errors in the awarding of employee rewards. This system application is only applied to determine the employee reward amount.